The Montado Great Route Sustainable tourism: treats and opportunities - Carriço, Cristina (2019)
Montado landscape is a highly valuated agro-forestry-pastoral system protected by law and integrated in the Portuguese Nacional List for Cultural Landscape World Heritage of UNESCO. It provides important environmental and cultural functions and services. These types of multifunctional landscapes are very attractive for sustainable tourism, like walking,birdwatching and other leisure activities. Alentejo Central is covered by montado landscapes (cork oak and holm oaktrees) in about 50% of its area. In 2016, the Comunidade Intermunicipal do Alentejo Central (CIMAC), decided tu implement a walking path network that connect the main villages and rural landscape and their cultural and natural heritage. lhe Montado Great Route (GRM), is planned for more than 1.000 km and connects natural, scenic, architectural and cultural values that everyone can enjoy walking through the landscape. These paths connect also with the contiguous regions namely to Alto and Baixo Alentejo, Vicentina Coast and Spain.